Determination of Didanosine in Pharmaceutical Dosage Forms by RP-HPLC - SHANTA KUMARI, A.; PRAKASH, K.; NAGOJI, K.E.V.; RAO, M.E.B. (Asian Journal of Chemistry, 2010)
A new reverse phase high performance liquid chromatographic (RPHPLC) method was developed and used for the estimation of didanosine (DDI) in bulk and pharmaceutical dosage forms using RPC-18 column using an isocratic HPLC system. The mobile phase consisted of acetonitrile and 0.05 M potassium dihydrogen phosphate (pH 4.2) in the ratio of 50 : 50 at a flow rate of 1 mL/min. The run time was 15 min. Nelfinavir mesylate (NEM) (50 μg/mL) was used as internal standard. The detection was carried out at 248 nm and the linearity was found to be in the range of 0.1-200 μg/mL. The retention times for didanosine and internal standard (NEM) were 3.183 and 10.675 min, respectively. Recovery studies shown that about 99.96 % of DDI could be recovered from the pre-analyzed samples indicating high accuracy of proposed method. There was no intra-day and inter-day variation found in the method of analysis. The mean drug content in branded DDI tablet dosage forms was quantified and found to be between 98.9 to 101.24 %.